Konsep Khalifah menurut Tafsir Al-Mishbah - Saifayurallah Saifayurallah (TAFSE: Journal of Qur'anic Studies, 2016)
This study aims to determine the use of the term caliph in the Qur'an. By using the thematic method, the writer finds that the word caliph is found in al-Baqarah verse 30 and Shad verse 26. In terms of language, the term Khalifah consists of three letters, namely kha ', lam and fa. The meaning contained in it there are three kinds, namely, changing position, later, and change. From this word, two different forms of the verb are found in the Qur'an, namely khalafa-yakhlifu which is used to mean "to replace", and "to make." In the two verses above, the use of the term caliph is explained not only limited to the caliphs after the Prophet Adam, who are referred to as humans with the task of prospering the earth which includes the task of calling on others to do good and prevent evil deeds. But the term caliph is also used for the leadership of the Muslims around the world, who will manage their affairs, both in the realm of religion and the world, as the successor and successor (khilafah) of the leadership of the Prophet Kajian ini bertujuan untuk mengetahui penggunaan terminologi khalifah dalam Al-Qur’an. Dengan menggunakan metode tematik, penulis menemukan kata khalifah terdapat di dalam al-Baqarah ayat 30 dan Shad ayat 26. Dilihat dari segi Bahasa, term Khalifah akar katanya terdiri dari tiga huruf yaitu kha’, lam dan fa. Makna yang terkandung di dalamnya ada tiga macam yaitu, mengganti kedudukan, belakangan, dan perubahan. Dari kata tersebut kemudian ditemukan dalam Al-Qur’an dua bentuk kata kerja yang berbeda yaitu khalafa-yakhlifu yang dipergunakan untuk arti “mengganti”, dan  “menjadikan.” Dalam dua ayat di atas, penggunaan term khalifah dijelaskan tidak hanya terbatas kepada para khalifah sesudah Nabi Adam, yang disebut sebagai manusia dengan tugas memakmurkan bumi yang meliputi tugas menyeru orang lain berbuat amar ma’ruf dan mencegah perbuatan mungkar. Namun terminologi khalifah juga digunakan pada pemegang kepemimpinan kaum muslimin di seluruh dunia, yang akan mengatur urusan mereka, baik dalam ranah agama maupun dunia, sebagai pengganti dan penerus (khilafah) kepemimpinan Nabi